Epstein-Barr virus type 2 infection is associated with higher viral loads in pediatric tonsils from western Kenya - Emmily Koech; Sidney Ogolla; Asito S. Amolo; Kevin Waomba; Ian Onditi; Katherine R. Sabourin; Bonface Ariera; Stellah Chumbe; Shannon C. Kenney; Rosemary Rochford; Gabriela Samayoa-Reyes (Microbiology Spectrum)
ABSTRACT Epstein-Barr virus (EBV) is an etiologic agent of endemic Burkitt lymphoma (BL), a prevalent pediatric cancer in sub-Saharan Africa. There are two known types of EBV, EBV Type-1 (EBV-1) and EBV Type-2 (EBV-2), both found in eBL patients. To determine the EBV load and type dynamics within the tonsils, saliva, whole blood, and plasma, we enrolled 102 children aged 1–14 undergoing tonsillectomy in a malaria holoendemic region of western Kenya. Additionally, we investigated EBV-2 cell type preference in tonsillar mononuclear cells (TMCs). Saliva, whole blood, and tonsillar tissue were collected at the time of enrollment. Whole blood was centrifuged to separate plasma from red blood cells, and tonsillar mononuclear cells (TMCs) were isolated from tonsils using a ficoll gradient. Using qPCR, we assessed EBV load and type in TMCs, plasma, whole blood, and saliva. Additionally, a subset of samples was subject to cell sorting to determine the infected cell population. We found that EBV loads were significantly higher in TMCs compared to whole blood (P < 0.01) and in saliva compared to plasma (P < 0.01). Children with EBV-2 exhibited higher EBV loads in TMCs (P = 0.016) than those with EBV-1. Both EBV types were detected in T-cells isolated from TMCS and were also observed in different compartments within the same individual. Our findings indicate that EBV-2 infection in tonsils is associated with higher viral loads, consistent with a model where EBV-2 has more lytic replication compared to EBV-1.IMPORTANCEThis study investigates Epstein-Barr virus (EBV) persistence in children residing in a malaria-endemic region of western Kenya. We examined the dynamic interplay of EBV viral load and type distribution across multiple host compartments: tonsils, saliva, whole blood, and plasma. Our key finding reveals significantly higher viral loads in pediatric tonsils infected with EBV-2 compared to EBV-1, providing novel insights into the phenotypic differences between EBV-1 and EBV-2. This suggests a greater propensity for lytic replication in EBV-2. We also observed the presence of both EBV types within the same individual, but in different compartments. Understanding the dynamics of EBV persistence, particularly the association of EBV-2 with increased tonsillar viral loads, is crucial. This knowledge sheds light on the pathophysiology of EBV infections and may indicate more severe or prolonged infections in affected children, ultimately contributing to improved risk assessment and management of EBV-associated diseases.